Implication of Negative Temperature in the Inner Horizon of Reissner-NordstrÃ¶m Black Hole - Yuant Tiandho (Institute for Research and Community Services (LPPM) ITB, 2017)
This paper reconsiders the properties of Hawking radiation in the inner horizon of a Reissner-NordstrÃ¶m black hole. Through the correlation between temperature and surface gravity, it is concluded that the temperature of the inner horizon is always negative and that of the outer horizon is always positive. Since negative temperature is hotter than any positive temperature, it is predicted that particle radiation from the inner horizon will move toward the outer horizon. However, unlike temperature, entropy in both horizons remains positive. Following the definition of negative temperature in the inner horizon, it is assured that the entropy of a black hole within a closed system can never decrease. By analyzing the conditions of an extremal black hole, the third law of black hole thermodynamics can be extended to multi-horizon black holes.